Petrologia, geocronologia (U-Pb SHRIMP) e geologia isotópica (Sm-Nd) do granito aquidabã- arco magmático amoguijá-terreno rio Apa- Sul do Cráton Amazônico - Nogueira, Shayenne Fontes (2015)
The Rio Apa Terrane is marked by a complex evolutionary history and still contain issues to be studied and understood. This paper presents the results obtained from the petrologic characterization of Aquidabã granite belonging to Intrusive Suite Alumiador inserted into the Magmatic Arc Amoguijá. In a previous context, this granite rocks were described as belonging to the Batholith Alumiador, however, they present unique characteristics that led to its individualization. The Aquidabã Granite is represented by plutonic and effusive rocks, acidic in nature. They are classified as dacites and rhyolites, rhyolites / alkaline rhyolites and adamelitos (monzogranites) / granite, divided in three petrographic facies: Graphic Granite (facies 1), Subvolcanic Dacitic-Riolítica (facies 2), Microgranito (facies 3). The first is volumetrically dominant in the body, arranged in the central portion of the Serra da Alegria; It characterized by massive rocks and pink , pink-gray, leucocratic, inequigranular thin.The facies 2 is characterized by the occurrence of rock types ranging from the dacites, dacites/riolitos. Have color grayish to brown, with phenocrysts of quartz and plagioclase, sometimes with dimensions between 1 and 7 mm, presenting features magmatic corrosion as gulfs and embayments, surrounded by a gray matrix felsítica.The rhyolites are pink-gray, massive, afaníticos with porphyritic varieties, with phenocrysts of alkali feldspar with sizes between 1 and 5 mm surrounded by a fringe spherulitic quartz K-feldspar + composition. The Microgranito facies (facies 3) is the smaller representation, found in the western and southwestern edges of the granite body, characterized by light gray massive rocks, thin inequigranular very thin. The geochemical data suggest a composite magmatism compatible with the granitic type A generated in magmatic arc environment in post-tectonic period. Through the method geochronological U-Pb (SHRIMP) was obtained zircon age ± 6.8 1811 Ma to Aquidabã Granite with εNd values (1,81Ga) of -2.18; -4.37 And -1.50, and TDM model age of 2.35, 2.57 and 2.26 Ga pointing to involvement of a crustal magma source in origin, possibly involving partial melting processes of continental crust neoarqueana the paeloproterozoica in granite generation. The results suggest that the Aquidabã Granite corresponds to a magmatism developed in the late Orosirian in Magmatic Arc Amoguijá.